Implementation of Industrialised Building System (IBS) in Construction Industry Malaysia: A Study in Perlis - Wong, Ng Ni (2021)
In Malaysia, the implementation of IBS still can be improved by giving encouragement among the developer in construction industry as there are still many states in Malaysia has very low IBS implementation such as Perlis. Therefore, it is importance for the government to have a plan to find out the way in increasing the IBS implementation. On the other hand, government must not only focus on encouraging the companies to implement IBS, but also need to focus on the percentage of the IBS manufacturer exist in Malaysia. If a lot of companies implement IBS but there is lack of IBS manufacturer also no point for the companies to implement it. The implementation of IBS will actually bring a lot of benefits to the companies such as faster completion for a project, waste reduction on site and reduce pollution on site. These will ensure the project that come out is more valuable. However, there are some barriers which cause a lot of developer companies not to implement this IBS such as high initial cost, available of cheap foreign labour, lack of technical knowledge, lack of creativity in design, etc. All these barriers cause the percentage of IBS implementation in Malaysia still need to be improved. Therefore, some strategies were figure out which can be used to enhance the implementation of IBS such as raising awareness, benchmark of IBS technology or maximize value of IBS. Lastly, all the data will collecting by literature review and quantitative research method. Then, will analyzed by quantitative data analysis.